(untitled) (Al-Qamar, 2020)
Domestic violence is one of the important problems among the social problems of present era; all the countries and societies are equally affected from it. In different Eras’s of history laws are formed for its prevention. Different conferences are held from the forum of UN and joint declarations are released to member countries to legislate for the prevention of domestic violence. In west there were different movements for the women rights, from this movement either women got some benefits but its harmful aspect was that women opposed the men. In family system the status of both men and women was of partner and ally. Despite of all the efforts for the prevention of domestic violence on international level, the reason for not reduction in it is the wrong diagnose of problem. On the contrary, hundreds of years ago Islam gave measures and instruction about the construction of family system and relationship between men and women, and in the light of these instructions a peaceful society can be formed. In this article reviewed the western society in regard of domestic violence. Especially for the prevention of domestic violence, analytical and research study of western and Islamic law is present. This research also explains the effective measures for its prevention. By following these measures a peaceful family system and society can be formed.